Geochemistry and petrogenesis of the Dehe Bala calc-alkaline granodiorites, south west of Boein Zahra - Zeynab Gharamohammadi; Ali Kananian (پترولوژی, 2016)
The Dehe Bala pluton is exposed approximately 45 km south-west of Boein Zahra town, Qazvin province. This Pluton which intruded the Eocene volcano-sedimentary rocks of the Urumieh-Dokhtar Magmatic assemblage (UDMA), is mainly composed of granodiorite and produced narrow thermal metamorphic contact aureoles surrounding the intrusion. The body is characterized by SiO2 content ranging from 64.2 to 66.9 wt%, high-k calc-alkaline nature and metaluminous character (A/CNK